Artificial Intelligence and Human Psychology in Online Transaction Fraud - Firdaus, Raheela; Xue, Yang; Gang, Li; Sibt e Ali, Muhammad (Frontiers in Psychology, 2022)
Banking operations has been changed due to technological advancement. On one side this modernization in technology facilitated banks in daily operation while on the other side, an increment in the number of cyber-attacks. Artificial intelligence introduced new models to detect and prevent the cybercrimes. Firstly, the research focused on fraud diamond theory and analyzed factors such as Rationalization, capabilities, perceived pressure and perceived opportunities in cybercrimes. Secondly, Artificial Intelligence (AI) characteristic explained by International Business Machine (IBM) Threat exposure, big data management, Explainability, Cost effectiveness and Risk prediction are evaluated to find their magnetism with risk reduction in banks. These characteristics were presented in the Watson learning platform. The research data is collected with the help of questionnaire by using likert five scales. Two tailed skewness and adoptive expert opinions are in line with the study hypotheses. The data is analyzed by using IBM SPSS SEM Software. The results proved that Fraud diamond theory and AI characteristics have positive and significant effect in cyber-crimes and risk reduction.